The co-production of urban food policies: Exploring the emergence of new governance spaces in three Spanish cities. (August 2021) - Vara-Sánchez, Isabel; Gallar-Hernández, David; García-García, Lidia; Morán Alonso, Nerea; Moragues-Faus, Ana
Highlights: Co-production of public policies has been analyzed in Córdoba, Madrid and Valencia. Widespread co-production of policies requires critical scrutiny to guide policymaking. The main condition for such multi-actor processes is to build collective trust. Collective construction of common spaces and codes of communication between actors is key. Ensuring the participation of producers in these processes is a main challenge. Abstract: City councils around the globe are developing food policies that aim to integrate different sectors and actors involved in delivering sustainability and food security outcomes fostering changes in policy-making processes. However, the co-production of public policies faces multiple drawbacks to establish new forms of governance that generate greater legitimacy for institutions, improved efficiency, tighter social cohesion and deeper democratisation. This paper draws on recent literature on social innovation and critical governance to portray food policy co-production processes in Cordoba, Madrid and Valencia, analysing the changing role of the actors involved, identifying key factors and tools that sustain co-production processes, and highlighting common barriers. The results illustrate the changing roles of key actors in co-productive policies, together with the need to acknowledge the diversity of knowledge, capacities and interests within the public sector and civil society organisations to design effective policies. This includes crafting formal and informal governance spaces that underpin the fluid and constantly evolving process of developing food policies. This comparative study, thus, contributes to progress in conceptual and practical debates on co-production, providing new insights to inform future urban food policy developments.